A new kinetic model for precipitation from solid solutions - Borysenko, O. (Condensed Matter Physics, 2015)
This model considers reversible elementary acts of migration of point defects (interstitials and/or vacancies) across the precipitate-matrix interface and enables one to derive equations for the rates of emission and absorption of solute atoms at the interface. The model predicts much stronger heterophase fluctuations and higher nucleation rates than the classical nucleation theory does. However, asymptotically, for large precipitate sizes and long ageing times, both models give the same results, being in agreement with the Lifshitz-Slyozov-Wagner theory of coarsening. В цiй моделi проведено розгляд оборотних елементарних актiв мiграцiї точкових дефектiв (мiжвузельних
атомiв та/або вакансiй) через мiжфазну границю видiлення-матриця, що дає змогу отримати рiвняння
для швидкостей вивiльнення та поглинання атомiв домiшки на границi. У порiвняннi з класичною теорiєю нуклеацiї, ця модель передбачає значно сильнiшi гетерофазнi флуктуацiї та бiльшi швидкостi нуклеацiї. Проте асимптотично, для великих розмiрiв видiлень та довгого часу старiння, обидвi моделi дають
однаковi результати, що збiгаються з результатами теорiї Лiфшиця-Сльозова-Вагнера.